The viability of the GPS precipitable water vapor In detecting drought-causing El Niño-southern oscillation at the Borneo Island - AbdulRahim, Farah Hani; Mohd. Ali, M.A.; Yatim, B.; Mandeep , J. S. (2012)
This paper explores the viability of incorporating GPS precipitable water vapor (PWV) and sea surface temperature anomalies (SSTa) at Niño 3, 3.4, and 4 regions in detecting drought-causing El Niño-Southern Oscillation. The proposed method consists of two tests, which reveal the beginning, ending, and duration of El Niño events. The first test, the Differential Anomalistic Determination, enables identification of months exceeding a threshold difference of 1.5 between PWV and SSTa. The second test, the Minor Shift in Standard Deviation, inputs constraints in the PWV anomaly percentage standard deviations to remove anomalistic peaks caused by systematic errors. Using PWV and SSTa data gathered from 2003 to 2007, the proposed method detected a drought-causing El Niño in 2006 a few months prior to the peak of the event. The 2006 El Niño recorded forest fires and lowest rainfall in the south of Borneo from August to November.